Endophthalmitis: Ursachen, Erreger, Therapie und Visusverlauf mit Fokus auf Glaukompatienten - Vorbeck, Julia; Hohberger, Bettina; Bergua, Antonio (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Endophthalmitis is one of the most serious emergencies in ophthalmology. In order to lower their prevalence, the most accurate knowledge of potential risk factors is important. Surgical therapy with targeted, pathogen-specific medication and an intact immune system are fundamental to preserve visual acuity. Furthermore, the question arises whether an unfavorable course can be predicted on the basis of underlying diseases of the eye, therefore a comparison between glaucoma patients (G) and non-glaucoma patients (NG) with regard to causative factors, pathogens, therapy and visual acuity course was drawn. Since a potential alteration of the local immune system in glaucoma disease has been described, it is of interest whether the clinical courses of endophthalmitis differ from non-glaucoma patients. Patients and methods A retrospective analysis of 75 eyes (13 G, 62 NG) who underwent treatment and surgery due to the diagnosis of endophthalmitis in the Department of Ophthalmology, University of Erlangen-Nuremberg has been evaluated over a period of 5 years. Clinical characteristics, surgical treatment, microbial spectrum and visual acuity in glaucoma and non-glaucoma eyes were investigated. Results A drastic vision impairment (44%) with inflammation of the anterior chamber (62.7%), hypopyon (52%) and reduced (40%) or complete missing sight (26.7%) of the fundus were predominantly present at first diagnosis in all patients. A previous eye surgery was observed in a total of 53%, especially cataract surgery. Gram-positive cocci were seen as the most common causing agent in both groups, (G: 23.1%; NG: 38.7%), whereas other rare pathogens were present only in glaucoma eyes. Pars-plana-vitrectomy was performed in 76% and enucleations in 20% of all patients, the latter significantly increased in glaucomateous eyes (p=0.01). A significant postoperative improvement of visual acuity was yielded in non-glaucoma patients (p<0.001); visual acuity outcome was worsen in glaucoma eyes. Conclusion Despite its rareness, early diagnosis and treatment of endophthalmitis is crucial for prognosis. In the present cohort, a worse visual acuity outcome was yielded in glaucoma patients in comparison to non-glaucoma patients.
CRIS-Team Scopus Importer:2022-08-05